A 32 FULL FACTORIAL DESIGN FOR TOPICAL CONTROLLED RELEASETAZAROTENE MICROSPONGE USING HPMC GEL - OZA, NISHANT; SAHOO, SATYAJIT; SAGAR, SWATI (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of present work was to the development of control release 0.1% tazarotene microsponge and incorporated into a HPMC K-100M gel. Methods: Drug compatibility with polymer was evaluated by FT-IR spectrum. Tazarotene microsponge was prepared by quasi-emulsion solvent diffusion method. On the basis of preliminary results, 32 full factorial design was employed to study the effect of Eudragit RS-100 conc. (X1) and PVA conc. (X2) on as particle size (Y1), % drug entrapment (Y2) and time required to 80% drug release (Y3). Multiple linear regression analysis, ANOVA and graphical representation of the influence factor by 3D plots were performed by using Sigma plot 11.0. In this study, the following constraints were arbitrarily used for the selection of an optimized batch: particle size<200 µm, drug entrapment>70 %, and time required to 80% drug release>360 min. The optimized formulation was subjected to SEM study. Tazarotene microsponge incorporates in 3% HPMC K-100M gel evaluated for viscosity, pH, drug content, spreadability, In vitro diffusion study, release kinetic study and photostability study. Results: The FT-IR result showed that there was no chemical interaction and SEM photograph indicates that microsponges are spherical and pores. From the results of multiple regression analysis, it was found that all factors had a statistically significant influence on all dependent variables. Conclusion: The optimized formulation of gel release kinetics having good linearity (R2= 0.987) of zero-order kinetic and it was found to be stable in the stability evaluation.